2021
DOI: 10.3390/met11111882
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Behavior of Wrought and EBAM Ti-6Al-4V under Scratch Testing

Abstract: The microstructure, mechanical properties, and deformation behavior of wrought and electron beam additive manufactured (EBAM) Ti-6Al-4V samples under scratching were studied. As-received wrought Ti-6Al-4V was subjected to thermal treatment to obtain the samples with microstructure and mechanical characteristics similar to those of the EBAM samples. As a result, both alloys consisted of colonies of α phase laths within prior β phase grains and were characterized by close values of hardness. At the same time, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…shown the formation of the HCP phase in the FCC matrix of a single crystal CoCrNi during nanoindentation [16]. The authors of the article, using MD simulation, demonstrated the development of reversible  phase transformations in the Ti-6Al-4V titanium alloy during scratch testing, which made it possible to explain the experimentally observed recovery of a scratch [17][18][19]. It has been found that the migration of the twin boundaries in the titanium crystallite under tension is also governed by the development of reversible  transformations [20].…”
Section: Experimental and Numerical Proceduresmentioning
confidence: 98%
“…shown the formation of the HCP phase in the FCC matrix of a single crystal CoCrNi during nanoindentation [16]. The authors of the article, using MD simulation, demonstrated the development of reversible  phase transformations in the Ti-6Al-4V titanium alloy during scratch testing, which made it possible to explain the experimentally observed recovery of a scratch [17][18][19]. It has been found that the migration of the twin boundaries in the titanium crystallite under tension is also governed by the development of reversible  transformations [20].…”
Section: Experimental and Numerical Proceduresmentioning
confidence: 98%